Comparative Study of Medical Replicas Generated By Computed Tomography Scan and Fused Deposition Modelling for Dimensional Error. (2020) - Naiju, CD.; Dev, Sidharth; Randev, S.; Rathee, Pooja
Abstract: In Additive Manufacturing Technology, Fused deposition modelling (FDM) is used for modelling, prototyping, and production applications. Purpose of this study is to determine the error generated in FDM fabricated hallux. An integrated approach of imaging technology, segmentation using Mimics software package and rapid prototyping technology were used in order to manufacture hallux replica. Human great toe (hallux) consists of 2 bones namely proximal and distal. CAD image of hallux was developed from CT image and it was compared with its corresponding FDM prototype. Visually, the prototype reproduces features of the original object. From the contour plot it was observed that majority of error were within -1 and 1 for distal and proximal hallux